STRATEGI DAN TANTANGAN PADA PENDEKATAN PASTORAL KONSELING UNTUK MEMBANTU REMAJA YANG MENJADI KORBAN BULLYING FISIK - Malini; Desi Rendealla (Anfa Mediatama, 2024)
This study examines strategies and challenges in implementing a pastoral counselling approach to support adolescent victims of physical bullying in Indonesia. With the increasing incidence of bullying, especially of a physical nature, there is an urgent need for effective interventions to address the negative impacts. The pastoral counselling approach was identified as a promising method in providing emotional and spiritual support, which is essential in the recovery process of victims. Through a literature review, this research explores how this approach can help victims cope with trauma, improve self-esteem, and embark on a journey of recovery. Analysis showed that the pastoral counselling approach was successful in providing psychological and spiritual support, despite challenges such as victims' reluctance to share their experiences and potential conflicts with religious beliefs. The results of this study provide important insights into pastoral counselling practice and suggest the need for strategies that are more inclusive and sensitive to the needs of victims of physical bullying. This research contributes to a better understanding of intervention approaches that can be applied in the Indonesian social and cultural context.